The Development of Academic Achievement and Participatory Learning Behaviors on “Our Community” through the Learning Together (LT) Collaborative Learning Technique for Grade 3 Students. - Khrutram, Narisa; Potiwan, Piyaluk; Suikraduang, Arun (Journal for Developing the Social and Community, 2026)
Background and Aims: Due to instructional problems in geography education for Grade 3 students, where students lacked teamwork and communication skills, resulting in a lack of interest in learning and low academic achievement. Therefore, the researcher aimed to apply the Learning Together (LT) cooperative learning management approach to enhance academic achievement and promote students' participatory behavior more effectively. Methodology: The research sample consisted of 27 Grade 3 students from Banphaengnongnuea School in the 2022 academic year, obtained through cluster random sampling. The experimental instruments were 10 learning activity plans on "Our Community" with an average appropriateness score between 4.59 and 4.76, representing the highest level. The data collection instruments included a 30-item, 3-option multiple-choice learning achievement test with a total reliability of 0.96, and a 15-item, 5-point rating scale assessment form for participatory behavior across 3 dimensions with an IOC range of 0.60–1.00. Data were analyzed using percentage, mean, standard deviation, and dependent samples t-test. Results: The learning achievement of students taught through the LT cooperative learning activities was statistically higher after the intervention than before at the .05 significance level. Additionally, the participatory behavior of students learning with the LT cooperative learning activities was overall at the highest level. () Conclusion: Learning management using the LT cooperative learning technique is a student-centered approach that aligns with social constructivist theory and the principle of positive interdependence. The group process, which emphasizes interaction and clear role distribution, not only enables learners to understand the content deeply but also effectively promotes their social skills and collaboration.